Seyyid Muhammad Riza and his essay “Seven Planets in the News of the Tatar Kings” - Ismagil Gibadullin; Il’nur Mirgaleev (Крымское историческое обозрение)
The article is about one of the most important works devoted to the history of the Crimean Khanate, the historical work “Seven Planets in the News of the Tatar Kings” (“As-sab’ as-sayyar fi akhbari muluk at-Tatar”) by the Ottoman author Seyyid Muhammad Riza, who most likely was of Crimean Tatar origin and came from the Seyid stratum and was part of the elite of the Ottoman Empire, in charge of the affairs of the Seyids. The title of the work has an allegorical meaning and is associated with the sacred meaning of the number seven and means “seven significant khans who ruled within the Crimea.” The work “As-sab‘ as-sayyar fi akhbari muluk at-tatar” was written between 1737–1747 and is an example of the chronicle genre (tawarikh) with a presentation of events in chronological order. In total, eight copies of the composition are known, which are stored in Turkey, Russia and Egypt. All of them were rewritten between 1755–1756 and 1791. The first publication of the original text of the work belongs to A.K. Kazembek.